Пошаговое объяснение:
c²-2,25-c²+64-2,5c+61,25=123-2,5c=123-2,5*2/3=123-5/3=121,33
1). a²-b²=(a-b)(a+b)
(1,5+c)(с – 1,5)=c²-1,5²
2) то же самое с²-8² но спереди стоит - поэтому -(с²-64)=-с²+64
3) с(а+б)=са+сб
-2,5(с-24,5)=-2,5с+61,25
дальше поставил 2/3 в "с" потом + - * : (можно с калькулятора)
Пошаговое объяснение:
c²-2,25-c²+64-2,5c+61,25=123-2,5c=123-2,5*2/3=123-5/3=121,33
1). a²-b²=(a-b)(a+b)
(1,5+c)(с – 1,5)=c²-1,5²
2) то же самое с²-8² но спереди стоит - поэтому -(с²-64)=-с²+64
3) с(а+б)=са+сб
-2,5(с-24,5)=-2,5с+61,25
дальше поставил 2/3 в "с" потом + - * : (можно с калькулятора)